Promoción turística para la agencia de viajes internacionales “Multicaribe”, y su incidencia en el cantón Quevedo. año 2014 - Mora Ballesteros, Kattia Del Rocio (2015)
This research was conducted with the objective of establish strategies for promoting tourism through international travel agency MULTICARIBE, and its incidence in Canton Quevedo, 2014. Through this project seeks to contribute to the development of Tourism City Quevedo, besides promoting it, both inside and outside of Ecuador considering the market study to be performed and the design of the processes to be followed. Different research techniques, starting with field observations in the travel agency Multicaribe, where tourists flock to request information about tourist attractions in the region was used. To gather information and interview survey was used, and then the data obtained were quantified and analyzed to obtain results that will test the hypothesis. From the results it was noted that there is little information about tourist attractions, especially with agencies to promote tourism, in the same way no sufficient resources are allocated to this effort.